Understanding Mathematical Concepts in the Missouri Mathematics Project Learning Model in terms of Student's Independent Attitude - Afniandari, Laily Noor; Supardi, Kasmadi Imam; Asikin, Mohammad (Universitas Negeri Semarang, 2021)
The learning objectives according to Permendiknas Number 22 emphasize that students could understand problems, design, and solve mathematical models, and interpret the solutions obtained. The objective will be the basis for students to become independent learners. Missouri Mathematics Project learning has a strong chance to achieve this goal.Therefore, this study aims to determine the effect of the Missouri Mathematics Project learning model on understanding mathematical concepts in terms of independent attitudes of fifth grade students. A combination research (Mixed Method) is used in this study by combining of Concurrent Embedded design. The sample in this study amounted to 58 students who were divided into two classes, namely the experimental class with 30 students and the control class with a total of 28 students. The results showed that there was an effect of the Missouri Mathematics Project learning model on understanding mathematical concepts in terms of the independent attitude of grade V students. This was indicated by the average percentage of understanding mathematical concepts by 63.1%. Students' understanding of mathematical concepts with the Missouri Mathematics Project learning model has been classically completed, are 73. The average independent attitude of students using the Missouri Mathematics Project learning model with an average percentage yield of 83.7%. Student independence has a significant effect on students' understanding of mathematical concepts by 10.6%, while the remaining 89.4% is influenced by other factors. It can be concluded that the Missouri Mathematics Project learning model affects the understanding of mathematical concepts in terms of students' independent attitudes.